2002
DOI: 10.3201/eid0802.010025
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Klebsiella pneumoniae Bacteremia: Global Differences in Clinical Patterns

Abstract: We initiated a worldwide collaborative study, including 455 episodes of bacteremia, to elucidate the clinical patterns of Klebsiella pneumoniae. Historically, community-acquired pneumonia has been consistently associated with K. pneumoniae. Only four cases of community-acquired bacteremic K. pneumoniae pneumonia were seen in the 2-year study period in the United States, Argentina, Europe, or Australia; none were in alcoholics. In contrast, 53 cases of bacteremic K. pneumoniae pneumonia were observed in South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
414
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(430 citation statements)
references
References 50 publications
8
414
2
6
Order By: Relevance
“…The non-specificity of K. pneumoniae for adherence to various host tissues is not surprising, given that this pathogen causes several kinds of infections, including pneumonia, bacteremia, urinary tract infection, and PLA. [1][2][3] Strains with the K1 and K2 capsular types have been identified as the predominant virulent types and are prevalent in K. pneumoniae PLA. 4,10 Moreover, brain and eyes are immune privileged sites; once these tissues are invaded by pathogens, brain and eyes would be highly susceptible to infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-specificity of K. pneumoniae for adherence to various host tissues is not surprising, given that this pathogen causes several kinds of infections, including pneumonia, bacteremia, urinary tract infection, and PLA. [1][2][3] Strains with the K1 and K2 capsular types have been identified as the predominant virulent types and are prevalent in K. pneumoniae PLA. 4,10 Moreover, brain and eyes are immune privileged sites; once these tissues are invaded by pathogens, brain and eyes would be highly susceptible to infection.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Recently, community-acquired pyogenic liver abscess (PLA) caused by K. pneumoniae has emerged, with 10-13% of PLA patients also exhibiting metastatic meningitis and/or endophthalmitis. [4][5][6][7][8][9][10] Mortality rates are 10% for those with K. pneumoniae PLA alone, and 30-40% among those with metastatic meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported that a minority of patients with Klebsiella liver abscess, and mostly from Taiwan, develop metastatic infection as manifested by endophthalmitis, uveitis, pneumonia, pulmonary abscess, pulmonary emboli, pulmonary abscess, pleural empyema, peritonitis, subcutaneous abscess, deep neck infection involving the mediastinum, splenic abscess, brain abscess, purulent meningitis, epidural abscess, renal abscess, prostate abscess, osteomyelitis, pyogenic arthritis and psoas abscess [7,8,[10][11][12][13][14][15][16][17][18]. This disease entity is called invasive liver abscess syndrome, which is caused by the hypervirulent K.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae has been reported to be the most common pathogen causing liver abscess in Korea [6,7]. The incidence of K. pneumoniae infection increases in immunocompromised conditions, such as diabetes mellitus, alcoholism, malignancy, hepatobiliary disease, chronic obstructive pulmonary disease, glucocorticoid therapy and renal failure [6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an emerging syndrome of community-acquired pyogenic liver abscess caused by highly virulent K. pneumoniae strains has occurred (Keynan et al, 2007;Ko et al, 2002;Lederman & Crum, 2005;Sobirk et al, 2010;Wang et al, 1998). These severe infections often occur in otherwise healthy individuals and are frequently complicated by devastating dissemination of the infection to the eyes and central nervous system.…”
Section: Introductionmentioning
confidence: 99%